2019
DOI: 10.7595/10.7595/management.fon.2019.0020
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces of Employees’ Entrepreneurial Intentions - Leadership Style and Organizational Structure

Abstract: Research Question: The purpose of this paper is to explore how leadership style and organizational structure characteristics influence employees’ intentions to start their own entrepreneurial ventures, ideas or projects, within an organizational setting. Motivation: The main goal is to learn how to prevent innovativeness declining in a traditional organization and make internal environment friendly for entrepreneurial initiatives and for employees with propensity to develop new ideas, aiming to create sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Additionally, it is concluded that organizational culture is responsible for the viability and development of organizations [9,20,44]. Existing research coincides with the conclusions that knowledge has to be present in all parts of the system as well as that an organic organizational structure, decentralization, and low formalization have positive effects on employee intentions [46].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Additionally, it is concluded that organizational culture is responsible for the viability and development of organizations [9,20,44]. Existing research coincides with the conclusions that knowledge has to be present in all parts of the system as well as that an organic organizational structure, decentralization, and low formalization have positive effects on employee intentions [46].…”
Section: Discussionsupporting
confidence: 63%
“…Knowledge has to be present in all parts of the system. [46]. Knowledge transfer is at a low level of efficiency among project team members in the Serbian banking sector.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…A large stream of literature studied the determinants of employee entrepreneurial orientation. Organizational variables were advocated such as management support (Mustafa et al, 2018 ; Sebora & Theerapatvong, 2010 ; ul Haq et al, 2018 ), job design (Mustafa et al, 2018 ), job autonomy (De Jong et al, 2015 ), proactive and pioneering leadership, decentralized and organic organizational structure (Nielsen et al, 2019 ), procedural justice and distributive justice (ul Haq et al, 2018 ). A more comprehensive study grouped those determinants into three categories: personal characteristics, job characteristics, and contextual characteristics (Kamil & Nasurdin, 2016 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Indeed, individual intrapreneurship identifies and exploits market opportunities that allow the organization to reinvent its offerings and strengthen its competitiveness (Neessen et al 2019). Employees' entrepreneurial activities flourish when they operate in an organic and flexible organizational structure (Nielsen et al 2019). Previous studies show that employee intrapreneurship is influenced by a myriad of factors such as managerial support (Lizote et al 2014;ul Haq et al 2018), engaging leadership (Nielsen et al 2019), job design (Mustafa et al 2018), and organizational justice (ul Haq et al 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Employees' entrepreneurial activities flourish when they operate in an organic and flexible organizational structure (Nielsen et al 2019). Previous studies show that employee intrapreneurship is influenced by a myriad of factors such as managerial support (Lizote et al 2014;ul Haq et al 2018), engaging leadership (Nielsen et al 2019), job design (Mustafa et al 2018), and organizational justice (ul Haq et al 2018). Ahmed et al (2020) posit that employees' engagement and their contribution to the business performance will be enhanced when an organization provides proper treatment to employees through management support, sufficient time to accomplish the work duties, the autonomy to work at the manager's own discretion, clear organizational boundaries, and a reward system for creativity and innovation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%